Tindak Tutur Direktif Pedagang di Pasar Tanah Abang - Rini Sriyanti (Universitas Indraprasta PGRI Jakarta, 2019)
The event of speech act that happen between buyer and seller in the market have important role, is to deliver the intention of some parties. Buyer and seller have same language as a means to deliver the intention in order to get the deal. The purpose of research is to describe form speech act and kind of speech act are using by seller and buyer to communication in Tanah Abang market. The object of research is speech act. The sample of dialogues are taking from 10 dialogues. The collecting of data research is observation attentively. The data are getting from note and record. Baside that, we areusing kind of speech act analysis of data. The result of research can be eplain, such as: 1) Tanah Abang are representative, directive, expressive, commissive, and declarative speech act, 2) Most of seller are using directive speech act in communication to persuade and influence the buyer at Tanah Abang market